Impact of the calcium form of β-hydroxy-β-methylbutyrate upon human skeletal muscle protein metabolism - Wilkinson, Daniel J.; Hossain, T.; Limb, Marie C.; Phillips, Bethan E.; Lund, J.; Williams, John P.; Brook, Matthew S.; Cegielski, Jessica; Philp, A.; Ashcroft, S.; Rathmacher, J.A.; Szewczyk, Nathaniel J.; et al. (Elsevier, 2017)
Background & aims: β-hydroxy-β-methylbutyrate (HMB) is purported as a key nutritional supplement for the preservation of muscle mass in health, disease and as an ergogenic aid in exercise. Of the two available forms of HMB (calcium (Ca-HMB) salt or free acid (FA-HMB)) – differences in plasma bioavailability have been reported. We previously reported that ∼3 g oral FA-HMB increased muscle protein synthesis (MPS) and reduced muscle protein breakdown (MPB). The objective of the present study was to quantify muscle protein metabolism responses to oral Ca-HMB.